A Quasi-Experiment to Investigating the Impact of the Strategy Design Pattern on Maintainability - Silva, Gabriel; Andrade, Vinícius; Ré, Reginaldo; Meneses, Rafael (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
GoF Design Patterns (DPs) are optimal solutions for several recurring problems in software development. As maintenance accounts for a massive amount of development costs, understanding the impact of DPs on maintainability is key to decide whether their benefits outweigh their costs. To test the hypothesis that the Strategy DP impacts maintainability, we carried out a quasi-experiment with 19 final-year undergraduate students. Participants performed enhancement tasks in two identical versions of Java classes that differed only in that a version implemented the Strategy DP whereas another version did not. As recommended in the literature, we used effectiveness as a representative proxy of maintainability and correctness as a measure of effectiveness. We found a statistically significant correctness change between treatments. Moreover, the effect size shows that a participant is 47.7 percentage points more likely to succeed when the Strategy DP is not used. Conversely, a participant is 5.5 times more likely to fail when the DP is introduced. Unlike most related studies, our findings suggest that the Strategy DP may reduce software maintainability although these findings need to be confirmed by independent and extended replications.